Effect analysis of neural network robot system in music relaxation training to alleviate adverse reactions of chemotherapy in patients with breast cancer - Teng, Yue; Bao, Jinlei; Li, Yinfeng; Ye, Haichun (Frontiers in Neurorobotics, 2023)
With the continuous progress of treatment methods, neural network and robot technology are more and more widely used in medical treatment. Postoperative chemotherapy for breast cancer is a common method to treat tumors, and prevent recurrence and metastasis, but during chemotherapy, it would cause many physiological and psychological side effects, such as gastrointestinal reactions, hair loss, anxiety, depression, etc., which would eventually lead to a continuous decline in the quality of life of patients. Music therapy is a common method used to relieve patients’ anxiety and pain in recent years. However, due to the lack of technology and algorithm support, the therapeutic effect of this therapy has not been particularly stable. This paper studied the effect of music relaxation training on alleviating the adverse reactions of chemotherapy in breast cancer patients with neural network robot system. First, it introduced the music therapy in the context of neural network robot system and the necessity of music relaxation training, and then summarized the positive role of music relaxation training in alleviating the adverse reactions of chemotherapy in breast cancer patients. Finally, it used neural network robot system to build a music therapy system. The experimental results showed that the new music therapy proposed in this paper has a good effect in alleviating the adverse reactions of chemotherapy in breast cancer patients, improving the cure rate by 7.84%, and also providing reference for the next development of neural network robot system in the medical field.